Role of the PLC-related, catalytically inactive protein p130 in GABA(A) receptor function - Kanematsu, Takashi (Oxford University Press, 2002)
The protein p130 was isolated from rat brain as an inositol 1,4,5-trisphosphate-binding protein with a domain organization similar to that of phospholipase C-δ1 but lacking PLC activity. We show that p130 plays an important role in signaling by the type A receptor for γ-aminobutyric acid (GABA). Yeast twohybrid screening identified GABARAP (GABA(A) receptor-associated protein), which is proposed to contribute to the sorting, targeting or clustering of GABA(A) receptors, as a protein that interacts with p130. Furthermore, p130 competitively inhibited the binding of the γ2 subunit of the GABA(A) receptor to GABARAP in vitro. Electrophysiological analysis revealed that the modulation of GABA-induced Cl(–) current by Zn(2+) or diazepam, both of which act at GABA(A) receptors containing γ subunits, is impaired in hippocampal neurons of p130 knockout mice. Moreover, behavioral analysis revealed that motor coordination was impaired and the intraperitoneal injection of diazepam induced markedly reduced sedative and antianxiety effects in the mutant mice. These results indicate that p130 is essential for the function of GABA(A) receptors, especially in response to the agents acting on a γ2 subunit.